Investigation of the Effects of Some Cardiovascular Drugs on Angiogenesis by Transgenic Zebrafish - Hui Lv; Bo Liu; Yongwen Qin (Mediators of Inflammation)
Introduction. Angiogenesis contributes to the pathophysiology of cardiovascular disease (CVD). Some cardiovascular drugs used in the treatment of CVD have an effect on the process of angiogenesis. Methods. Transgenic Tg (flk1: EGFP) zebrafish embryos were used to identify the effects of some cardiovascular drugs on angiogenesis during vertebral development in vivo. Zebrafish embryos at a one-cell stage or two-cell stage were cultured with embryo medium containing cardiovascular drugs at a final solvent concentration of 0.5% (V/V) dimethyl sulfoxide (DMSO) for 24 hours in 24-well plates. Results. We found that 6 drugs including isosorbide mononitrate, amlodipine, bisoprolol fumarate, carvedilol, irbesartan, and rosuvastatin calcium may affect angiogenesis by vascular endothelial growth factor (VEGF) signaling pathway. Conclusion. These new findings of some cardiovascular drugs should improve the treatment of cardiovascular diseases.